2020
DOI: 10.26452/ijrps.v11i1.1953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ginger tea on chemotherapy-induced nausea and vomiting among cancer patients in selected hospitals, Bhubaneswar, Odisha

Abstract: A quasi-experimental research study (posttest only research design) was conducted to evaluate the effect of ginger tea on chemotherapy-induced nausea and vomiting among cancer patients in selected hospitals of Bhubaneswar and to find out the association of level of chemotherapy-induced nausea and vomiting with selected socio-demographic variables. For this study, a quantitative experimental approach and post-test only research design was adopted. 100 patients were selected by convenience sampling technique and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This is one of the few experimental studies conducted to evaluate the antiemetic effect of ginger tea in preventing chemotherapy-related nausea and vomiting in gynecological cancers. The results showed that ginger tea had a significant beneficial effect in reducing the experience, development, and distress of nausea, vomiting, and retching induced by cisplatin-based regimens, which is consistent with 1 study conducted in India 5 . A controlled trial in patients with gynecological cancer receiving cisplatin-based regimens also showed that 1.0 g of ginger reduced delayed nausea and vomiting as effectively as 40 mg metoclopramide per day but had no effect on preventing acute nausea and vomiting 23 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This is one of the few experimental studies conducted to evaluate the antiemetic effect of ginger tea in preventing chemotherapy-related nausea and vomiting in gynecological cancers. The results showed that ginger tea had a significant beneficial effect in reducing the experience, development, and distress of nausea, vomiting, and retching induced by cisplatin-based regimens, which is consistent with 1 study conducted in India 5 . A controlled trial in patients with gynecological cancer receiving cisplatin-based regimens also showed that 1.0 g of ginger reduced delayed nausea and vomiting as effectively as 40 mg metoclopramide per day but had no effect on preventing acute nausea and vomiting 23 .…”
Section: Discussionsupporting
confidence: 89%
“…The results showed that ginger tea had a significant beneficial effect in reducing the experience, development, and distress of nausea, vomiting, and retching induced by cisplatin-based regimens, which is consistent with 1 study conducted in India. 5 A controlled trial in patients with gynecological cancer receiving cisplatin-based regimens also showed that 1.0 g of ginger reduced delayed nausea and vomiting as effectively as 40 mg metoclopramide per day but had no effect on preventing acute nausea and vomiting. 23 This effectiveness has been confirmed by some studies, although others have shown contrary results.…”
Section: Ginger Tea Effect On Nausea and Vomiting In The Intervention...mentioning
confidence: 99%
See 3 more Smart Citations